2009
DOI: 10.1080/14786410701852826
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites ofAspergillussp. F1, a commensal fungal strain ofTrewia nudiflora

Abstract: Twelve compounds that belonged to five structure types, namely saturated dibenzylbutyrolactone lignans (1-3), sesterterpenoids (4-6), anthraquinone (questin, 7), benzophenone (dihydrogeodin, 8) and diphenyl ethers (9-12), were isolated from the extract of the strain Aspergillus sp. F1, which was isolated from the seeds of Trewia nudiflora. Among them, compounds 1, 11 and 12 were determined to be new, namely butylrolactone-V, butyl 2,4-dichloroasterrate and methyl 2,4-dichloroasterrate, respectively. The struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…Analysis of the 1 H-1 H COSY spectra revealed two partial structures C-1 to C-2 and C-9 to C-11 ( Figure 2). The 13 C-1 H long range couplings of 2J and 3J observed in the 13 The cross peak from 15-OCH 3 (d 3.52) to C-15 (d 173.0) supported the partial structure III. (4) The cross peaks from 14-H to C-15 and from 24-H 3 to C-16 indicated that the partial structures I, II and III are connected as shown in Figure 2.…”
supporting
confidence: 54%
“…Analysis of the 1 H-1 H COSY spectra revealed two partial structures C-1 to C-2 and C-9 to C-11 ( Figure 2). The 13 C-1 H long range couplings of 2J and 3J observed in the 13 The cross peak from 15-OCH 3 (d 3.52) to C-15 (d 173.0) supported the partial structure III. (4) The cross peaks from 14-H to C-15 and from 24-H 3 to C-16 indicated that the partial structures I, II and III are connected as shown in Figure 2.…”
supporting
confidence: 54%
“…This assignment was further supported by 1 H- 1 H COSY correlation between H-1‴ and H-2‴, and HMBC correlations from H-1‴ to C-2′, C-4′ and C-3‴, from H-4‴/5‴ to C-2‴ and C-3‴ (Figure 2). The dextral specific rotation ([α] 25 D +71) indicated R -configuration at C-4 [17]. Thus, the structure of terrelactone ( 3 ) was determined as ( R )-methyl 4-hydroxy-2-(4-hydroxy-3-(3-hydroxy-3-methylbutyl)benzyl)-3-(4-hydroxyphenyl)-5-oxo-2,5-dihydrofuran-2-carboxylate.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of compounds 5 – 11 were elucidated by the comparison of their MS and NMR data with those reported in literature, and they were identified as: butyrolactone II ( 5 ) [ 19 ], butyrolactone IV ( 6 ) [ 10 ], butyrolactone III ( 7 ) [ 20 ], butyrolactone IX ( 8 ) [ 21 ], 3-hydroxy-5-[[4-hydroxy-3-(3-methyl-2-buten-1-yl) phenyl] methyl]-4-(4-hydroxyphenyl)-(5 H )-furan-one ( 9 ) [ 6 ], 5-dihydro-4-hydroxy-2-[[4-hydroxy-3-(3-methyl-2-butenyl) phenyl] methyl]-3-(4-hydroxyphenyl)-5-oxo-furancarboxylic acid) ( 10 ) [ 22 ], butyrolactone I ( 11 ) [ 23 ]. Their 1 H and 13 C NMR were provided in Tables S1 and S2 in the Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%